COVID‐19‐related anxiety predicts somatic symptoms in the UK population. Issue 4 (27th May 2020) - Shevlin, Mark; Nolan, Emma; Owczarek, Marcin; McBride, Orla; Murphy, Jamie; Gibson Miller, Jilly; Hartman, Todd K.; Levita, Liat; Mason, Liam; Martinez, Anton P.; McKay, Ryan; Stocks, Thomas V. A.; et al.
Abstract : This study aimed to estimate the association between anxiety associated with COVID‐19 and somatic symptoms, using data from a large, representative sample ( N = 2, 025) of the UK adult population. Results showed that moderate to high levels of anxiety associated with COVID‐19 were significantly associated with general somatic symptoms and in particular with gastrointestinal and fatigue symptoms. This pattern of associations remained significant after controlling for generalized anxiety disorder (GAD), pre‐existing health problems, age, gender, and income. This is the first evidence that anxiety associated with COVID‐19 makes a unique contribution to somatization, above and beyond the effect of GAD.